The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1371/journal.pone.0016199
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Frataxin: An Essential Function for Cellular Viability through an Interaction with a Preformed ISCU/NFS1/ISD11 Iron-Sulfur Assembly Complex

Abstract: BackgroundFrataxin, the mitochondrial protein deficient in Friedreich ataxia, a rare autosomal recessive neurodegenerative disorder, is thought to be involved in multiple iron-dependent mitochondrial pathways. In particular, frataxin plays an important role in the formation of iron-sulfur (Fe-S) clusters biogenesis.Methodology/Principal FindingsWe present data providing new insights into the interactions of mammalian frataxin with the Fe-S assembly complex by combining in vitro and in vivo approaches. Through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
258
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(275 citation statements)
references
References 39 publications
17
258
0
Order By: Relevance
“…Only recently it was demonstrated that FXN associates with the early components of the mitochondrial Fe-S cluster biogenesis pathway, NFS1 and ISCU 2,23 . It was then reported that in the presence of ISCU, mammalian FXN stimulates sulfide production by NFS1 and this was correlated with stimulation of Fe-S cluster assembly 11,14 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only recently it was demonstrated that FXN associates with the early components of the mitochondrial Fe-S cluster biogenesis pathway, NFS1 and ISCU 2,23 . It was then reported that in the presence of ISCU, mammalian FXN stimulates sulfide production by NFS1 and this was correlated with stimulation of Fe-S cluster assembly 11,14 .…”
Section: Discussionmentioning
confidence: 99%
“…The ISC machinery comprises ISCU, a scaffold protein on which Fe-S clusters are assembled, NFS1, a pyridoxal phosphatedependent cysteine desulfurase, ISD11 and FXN [20][21][22][23] . The eukaryotic ISC machinery has evolved from bacteria and thus some of the primary steps of Fe-S cluster assembly have been conserved 16,24,25 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…17 and 18). Whereas oligomeric FXN forms stable complexes with NFS1-ISD11 in the absence or presence of ISCU (15), monomeric FXN 81-210 only binds to a preformed NFS1-ISD11-ISCU complex (15,16,19). Both isoforms are normally present in cultured cells and tissues and are thought to ensure incremental rates of iron-sulfur cluster synthesis depending on iron availability and metabolic requirements (8).…”
mentioning
confidence: 99%
“…Yfh1, the yeast frataxin homolog, has been proposed to serve as an iron donor and/or a regulator of Nfs1 function (9-11). Isu, Nfs1, and Yfh1 can bind with one another to form a so-called "Fe-S cluster assembly" complex (11)(12)(13). Transfer of the assembled clusters to recipient proteins requires a specialized Hsp70 chaperone system composed of the Hsp70 Ssq1 and the J-protein cochaperone Jac1, as well as the nucleotide release factor Mge1 (14,15).…”
mentioning
confidence: 99%